Predictors of atrial fibrillation after off pump coronary artery bypass graft-a prospective observational study - Chooriyil, Nidheesh; Pillai, Manjusha N.; Jayakumar, Thanath K. N. (International Surgery Journal, 2021)
Background: Postoperative atrial fibrillation (AF) is a common and potentially morbid complication following coronary artery bypass graft (CABG) surgery. Many factors have been suggested to increase the incidence of post-operative AF after CABG. Objective was to estimate the proportion of patients developing AF after off pump CABG (OPCABG) and to determine the possible predictors of AF after OPCABG. Methods: This was a prospective observational study done in the department of Cardiovascular and Thoracic Surgery of a tertiary center from December 2019 to December 2020 after obtaining Institutional review board clearance. A sample size of 334 was fixed and patients undergoing OPCABG were consecutively recruited in the study. The association of preoperative and postoperative factors with occurrence of AF were analysed using the univariate analysis with a p value <0.05 using the SPSS 16 software. Multivariate analysis was done to determine the independent predictors after OPCABG. Results: In this prospective study amongst the 334 patients recruited 60 (18%) developed atrial fibrillation and the maximum incidence was seen on the third postoperative day. Patients who developed AF were older with mean age of 61.38±7.63 years, 2.96 (95% CI 0.71-5.21) as compared to those who did not develop AF. Male gender Odds ratio 1.17 (95%CI 1.06-1.31), low ejection fraction 54.95±10.47, -3.25 (95% CI-5.99- -0.52); large atrial size 3.45±0.42, 0.12 (95% CI 0.02-0.06); long intensive care unit (ICU) stay 2.47±0.59, 0.32 (95% CI 0.06-0.21) and long hospital stay 7.62±3.36, 1.48 (95% CI 0.44-0.59) were associated with development of AF after OPCABG. Older age was found to be an independent predictor of development of AF on doing multivariate analysis. Conclusions: In our study advanced age was found to be an independent predictor of atrial fibrillation after OPCABG. Males, low ejection fraction, large atrial size and longer ICU and hospital stays were associated with occurrence of AF after OPCABG.